Current and future approaches for in vitro hit discovery in diabetes mellitus. Issue 10 (October 2022) - Zhang, Xin; Kupczyk, Erwin; Schmitt-Kopplin, Philippe; Mueller, Constanze
Highlights: An overview of current and future drug targets in T2DM and how to access these with classic in vitro assays. Emerging HTS technologies for small-molecule drug discovery like HCS and metabolomics/lipidomics are summarized. Applications are highlighted and findings of multiparameter HCS and metabolomics/lipidomics in T2DM are summarized. Providing strategies on how to deal with the complex diseases in in vitro screens and introducing the concept of hit discovery by advanced phenotyping. Abstract : Type 2 diabetes mellitus (T2DM) is a serious public health problem. In this review, we discuss current and promising future drugs, targets, in vitro assays and emerging omics technologies in T2DM. Importantly, we open the perspective to image-based high-content screening (HCS), with the focus of combining it with metabolomics or lipidomics. HCS has become a strong technology in phenotypic screens because it allows comprehensive screening for the cell-modulatory activity of small molecules. Metabolomics and lipidomics screen for perturbations at the molecular level. The combination of these data-intensive comprehensive technologies is enabled by the rapid development of artificial intelligence. It promises a deep cellular and molecular phenotyping directly linked to chemical information about the applied drug candidates or complex mixtures.